(untitled) (Italian Journal of Public Health, 2004)
Public health professionals are aware of the global imbalance between the range of factors that affect human health and the inadequate structures in place to address them. Global integration is moving at a rapid pace, fuelled by faster communication and greater movement of people and ideas. Yet the world continues to use nineteenth century structures based on individual nation states. The rapid pace of change requires new solutions, with effective international co-operative action, with devolved decision making that ensures implementation.The international agencies that should be able to tackle these issues have had limited success. There are examples of governments coming together to address some global problems related to health, such as recent conferences on reproductive health, the conference on climate change in Kyoto and the treaty on landmines.However, this is not sufficient, and implementation of agreements remains a barrier to progress.